Enzymatic Interesterification of Crude Palm Oil with Methyl acetate: Effect of Pre-treatment, Enzyme’s Dosage and Stability - Muhammad Zarin Amin Zainal; Andri Cahyo Kumoro; Ratna Dewi Kusumaningtyas; Haniif Prasetiawan; Dhoni Hartanto; Harumi Veny; Fazlena Hamzah; Miradatul Najwa Muhd Rodhi (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
In the present study, biodiesel was produced via the enzymatic interesterification of Crude Palm Oil (CPO) and methyl acetate within ultrasonic condition. In contrast to alcohol, methyl acetate as an acyl acceptor does not inhibit lipase activity and can create triacetin as a useful byproduct.  In this work, Immobilized lipase from Candida Antartica A (CaLA) was utilized as biocatalyst and the effect of using non-pretreated CPO and pre-treated CPO as feedstock were explored. The pre-treatment of CPO involves degumming with acid, washing with water, and bleaching. The enzymatic interesterification was conducted in three-neck flasks using an ultrasonic water bath at 45o C.  Few parameter effects on biodiesel production were also investigated, including the effect of molar ratio of CPO to methyl acetate, the effect amount of lipase, and the reusability of immobilized lipase (CaLA) in the interesterification reaction.  The highest average Biodiesel yield of 80.6% was obtained from pretreated CPO at a molar ratio of 1:9 with 100 mg (1% w/v) of Immobilized CaLA, after three hours of reaction. Further research on the reusability of immobilized CaLA revealed that the yield of biodiesel reduced significantly after the second run. The results of the present study also demonstrated that Immobilized CaLA performed well at low concentrations but had low stability, with productivity decreasing to 92% upon reuse after the initial run. In order to make Immobilized lipase economically viable, further research must be conducted to overcome its low stability in the reaction.